How Costly is using Livestock as a Saving Device? A Note on Meat Prices during Food Shortages - Wouter Zant (Tinbergen Institute, 2020)
We measure if and to what extent livestock sales during food shortages affect the wealth value of livestock. For this purpose we exploit monthly market prices of meat and staple foods in Malawi, for up to 72 locations (towns, villages and markets), for the period from January 1991 to December 2009. The empirical evidence is consistent with increased livestock sales during food shortages, especially small livestock, and especially in the south. Results are robust for different ways to approximate food shortages and various other threats. During food shortages, real meat prices in local markets tend to decrease up to 40%, thereby reducing the wealth value of livestock at the very moment livestock is sold on the market to purchase staple foods. Similar to staple foods, poor agricultural households systematically tend to sell low and buy high. Savings instruments to bridge food shortage periods that do not lose value when liquidated, are needed. Currently popular index insurance, if properly designed to take account of this, or well-functioning safety nets will generate large welfare gains and enhance economic growth.
Keywords: D19; O16; 330; food security; saving; drought; livestock; subsistence farming; Malawi; Africa